2018
DOI: 10.1111/cga.12268
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor Foxc1 is involved in anterior part of cranial base formation

Abstract: The cranial base is a structure mainly formed through endochondral ossification and integrated into the craniofacial complex, which acts as an underlying platform for the developing brain. Foxc1 is an indispensable regulator during intramembranous and endochondral ossification. In this study, we found that the spontaneous loss of Foxc1 function in a mouse (congenital hydrocephalous), Foxc1 , demonstrated the anterior cranial base defects, including unossified presphenoid and lack of middle part of the basisphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…In our research, we revealed that the upregulation of Foxc1 expression appeared at an early stage in osteogenic differentiation in vitro. Researchers also found that Foxc1 was detected in ectoderm and craniofacial mesenchyme of mouse embryos at E8.5 and in the first zygomatic arch at E9.5, while Runx2 was detected in the osteogenic precursor matrix at E10.5, suggesting the potential regulating effect of Foxc1 on Runx2 in osteogenic differentiation (Sun et al, 2013a;Mya et al, 2018b). Such hypothesis was confirmed by luciferase reporter assay, and it turned out that Foxc1 could enhance the transcriptional activity of Runx2.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In our research, we revealed that the upregulation of Foxc1 expression appeared at an early stage in osteogenic differentiation in vitro. Researchers also found that Foxc1 was detected in ectoderm and craniofacial mesenchyme of mouse embryos at E8.5 and in the first zygomatic arch at E9.5, while Runx2 was detected in the osteogenic precursor matrix at E10.5, suggesting the potential regulating effect of Foxc1 on Runx2 in osteogenic differentiation (Sun et al, 2013a;Mya et al, 2018b). Such hypothesis was confirmed by luciferase reporter assay, and it turned out that Foxc1 could enhance the transcriptional activity of Runx2.…”
Section: Discussionmentioning
confidence: 89%
“…Meanwhile, the regulation of osteogenesis usually involves the collaborative activities of several signaling proteins and transcription factors (Hopkins et al, 2016b). Foxc1, which belongs to the transcription factors family named as Forkhead box or FOX genes, has an essential impact on regulation of intramembranous and endochondral ossification in normal development and bone formation (Mya et al, 2018a). Foxc1 null embryos displayed bony fusion of maxilla and mandible, accompanied by defects in maxilla, mandible, and agenesis of the temporomandibular joint (Inman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, knockout of either gene in mice mildly affects the formation of the middle ear, 3,4,30 and Foxc2 −/− mice exhibit a small otic capsule, but this does not seem to be a severe deformation 4 . As for the cranial base, Foxc2 −/− mice show non‐ossification of the presphenoid, 3,4 while Foxc1 ch/ch mice exhibit non‐ossification of the presphenoid, severe loss in the anterior part of the basisphenoid, and a deformed alisphenoid 31 . Based on these phenotypes, together with the similar expression profile of these genes, it is suggested that Foxc1 plays a more vital role in basisphenoid and alisphenoid development than Foxc2 , while the two genes are equally responsible for the development of other cranial base components in which they are co‐expressed.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Foxc1 and Foxc2 demonstrate cooperative activity during embryogenesis of the eye, 19 kidney, 20 heart, 21 and vasculature 15,22‐25 . The roles of Foxc1 in craniofacial development has been relatively well‐investigated 12‐14,26‐31 . In contrast, although Foxc2 participates in craniofacial morphogenesis, 3,4 the detailed functioning of Foxc2 in this region has yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…PITX2 protein plays a critical role in early development of structures in the front part of the eye, as well as the pituitary cells, teeth, heart, and abdominal organs (Franco et al, 2014). FOXC1 protein is a transcriptional partner of GLI2 highly expressed in undifferentiated mesenchyme and is thought to play a regulator role in chondrogenesis, initiating the ossification of cranial base bones important for craniofacial morphogenesis (Mya et al, 2018; Yoshida et al, 2015).…”
Section: Discussionmentioning
confidence: 99%